Qualidade de vida de cirurgiões-dentistas que atuam no serviço público - Rovida, Tânia Adas Saliba [UNESP]; Saliba, Nemre Adas [UNESP]; Lima, Daniela Pereira [UNESP]; Garbin, Cléa Adas Saliba [UNESP]; Moimaz, Suzely Adas Saliba [UNESP] (My University, 2013)
Introduction: The quality of life of dentists has worsened over time, due to increased risks of labor and competitiveness in the labor market. However, there are only few studies about it. Objective: Investigate the perception of quality of life of dentists working in public service. Methods: In order to accomplish that, a cross-sectional study survey was conducted with 52 dentists of the professional permanent staff of the Municipal Health Service. The data were collected through structured questionnaire, validated, self-administered, proposed by the World Health Organization (WHO) in its shortened version, WHOQOL-Bref. Descriptive statistics and multiple regression were conducted, taking 95% as the confidence interval that characterizes the sample and the calculation of scores for each domain. Results: There was predominance of female subjects (76.9%) the majority of them aged 25 to 35 years (48.7%). Most professionals consider their quality of life good (82.7%), and were satisfied with their health (71.2%). Considering the measures of central tendency and dispersion, the physical domain (13.8) and Environment (13.8) had the lowest mean scores. All areas affected equally poor quality of life of research participants. The facets that showed the lowest values were the physical environment with 39.71 points and 53.92 points to financial resources. Conclusion: The majority of professionals were satisfied with their health and considered their quality of life good.

Introdução: A qualidade de vida dos cirurgiões-dentistas tem piorado ao longo do tempo, em função do aumento dos riscos laborais e da competitividade no mercado de trabalho. Entretanto, existem poucos estudos na literatura que abordam o tema com essa parcela de profissionais da área da saúde. Objetivo: Conhecer a percepção dos cirurgiões dentistas que atuam no serviço público a respeito da sua qualidade de vida. Métodos: Foi realizado um estudo transversal tipo inquérito com 52 cirurgiões-dentistas do quadro permanente de saúde municipal. Os dados foram coletados por meio de questionário estruturado, validado, autoaplicado, proposto pela Organização Mundial de Saúde (OMS), na sua versão abreviada WHOQOL-Bref. Foram efetuadas estatística descritiva e regressão múltipla, adotando-se intervalo de confiança de 95%, caracterização da amostra e cálculos dos escores de cada domínio. Resultados: Pode-se observar predominância de sujeitos do sexo feminino (76,9%), com concentração de idade entre 25 e 35 anos (48,7%). A maioria dos profissionais considerou sua qualidade de vida boa (82,7%) e estavam satisfeitos com sua saúde (71,2%). Considerando as medidas de tendência central e dispersão, os domínios Físico (13,8) e Meio Ambiente (13,8), apresentaram a média de escores mais baixa. Todos os domínios influenciaram de forma igualitária a má qualidade de vida dos participantes da pesquisa. As facetas que apresentaram os menores valores foram as de ambiente físico, com 39,71 pontos, e recursos financeiros, com 53,92 pontos. Conclusão: A maioria dos profissionais encontravam-se satisfeitos com sua própria saúde e consideravam sua qualidade de vida boa.
Quality of life of dentists working in the public service
Keywords: Quality of life; Dentists; World Health Organization; Qualidade de vida; Odontólogos; Organização Mundial da Saúde